Factors affecting purchasing process of digestate: Evidence from an economic experiment on Sicilian farmers' willingness to pay - Gioacchino Pappalardo; Roberta Selvaggi; Salvatore Bracco; Gaetano Chinnici; Biagio Pecorino (Agricultural and Food Economics, 2018)
In this study, we evaluate from the perspective of the theory of commitment costs if the level of farmer understanding about digestate attributes could influence the willingness to pay (WTP) for it. For this purpose, we carried out a research on a sample of 223 Sicilian farmers to correlate their WTP for digestate with a set of eight attributes which usually characterise organic soil conditioners. An experimental design was set up so that participants were given different waiting times to decide on their WTP and different levels of information on the attributes of organic soil conditioners. The results highlight a positive WTP, but farmers are strongly influenced by how much information is available on digestate. Without it, farmers' WTP decreases drastically probably due to phenomena correlated to what economic theory calls commitment costs.
Keywords: 330; Willingness to pay; Digestate; Experimental auction; Commitment costs